HUBUNGAN ANTARA FAKTOR PERSONAL HYGIENE DAN KONDISI LINGKUNGAN FISIK RUMAH DENGAN KEJADIAN KUSTA (Studi Kasus Di Wilayah Kerja Puskesmas Teluk Batang Kabupaten Kayong Utara) - Rochmawati; Trisnawati , Elly; Radiantini , Yuyun Pramita (JURNAL BORNEO AKCAYA, 2014)
Leprosy is a chronic infectious disease caused by mycobacterium leprae. This bacteria attacks the nervous edge, skin, mucosa, respiratory tract, reticuloendothelial system, eyes, muscles, bones, and testicles. In Indonesia, in 2012, Case Detection Rate (CDR) of this disease amounted to 6.30 per 100,000 population. In West Kalimantan, the CDR is 1.50 per 100,000 population. While the CDR in Kabupaten Kayong Utara was 24.4 per 100,000 population. Surprisingly, the number of CDR at Puskesmas Teluk Batang Kabupaten Kayong Utara was 90,2 per 100,000 population. This study is aimed at figuring out the correlation of personal hygiene, home condition, and leprosy cases (a case study at work area of Puskesmas Teluk Batang Kabupaten Kayong Utara). An observational analytic method and case control design were carried out in this study. The number of the respondents was 57 respondents, consisting of 19 case group and 38 control group. Both case and control group sampling were selected by using matching technique which included age, sex and residence area. Then, the data was analyzed by using univariate and bivariate analysis, and chi square test. The study revealed two findings. First, there were correlation of behavior of sharing a single towel (p value = 0,007 ; OR =10,500), natural light of the bed rooms (p value = 0,001 ; OR =9,022), natural light of the living room (p value = 0,001 ; OR =9,022), humidity of the bedrooms (p value = 0,000 ; OR =18,417), temperature of the living rooms (p value = 0,002; OR =0,046), density of the bedroom occupancy (p value = 0,006 ; OR =6,067) and the incidence of leprosy. Second, there were no correlation of bed room ventilation, living room ventilation, bed room temperature, and the incidence of leprosy. Based on the findings, the local health workers are encouraged to organize team and program in order to break the chain of leprosy, including early detection, treatment, and rehabilitation. Besides, the people are recommended to have regular check up, keep the healthy personal hygiene, and increase the house condition healthily.